Impulsive noise mitigation in Haar DWT based OFDM systems - Ali, Moaaz Elhag; Abdullah, Khaizuran; Siddiqi, Mohammad Umar; Ismail, Ahmad Fadzil (2013)
In this work, a simple mitigation technique for the effect of impulsive noise in Haar discrete wavelet transform (DWT) based OFDM systems is presented. Based on the analysis for a certain configuration of Haar DWT-OFDM, redundancy in the transmitted samples was found and exploited to mitigate the impulsive noise by replacing the corrupted samples. Under the assumption of Bernoulli-Gaussian model for impulsive noise, the proposed technique is efficient with low probability of impulse occurrence (p). With p = 0:001 and BPSK scheme, it can achieve BER of 10